Investigar y desarrollar una guía metodológica de los mecanismos de transición y coexistencia ipv4-ipv6 en el área de sistemas de la facultad de ingeniería de la universidad nacional de Chimborazo - Ramírez Mosquera, Danilo Enrique (2010)
The Internet Protocol version 4 (IPv4) has been the main agent of development and expansion of Internet in recent decades. Internet service with client-server model is based on a central computer network administration which multiple clients access, where the email service or email is one of the most used. Are generally used to send SMTP mail messages, and POP3 or IMAP4 to obtain messages. In addition, each day is more common the need to post or transmit audio and video over the Internet and / or Intranets. Multimedia transmission is based on the model is also based on the client-server.